Informality and the context of reception in South Africa's new immigrant destinations. Issue 3 (30th October 2017) - Theodore, Nik; Pretorius, Anmar; Blaauw, Derick; Schenck, Catherina
Abstract: This study examines the context of reception for Zimbabwean migrants who are engaged in South Africa's informal economy. It seeks to contribute to two areas of migration scholarship: (a) the emergence of new immigrant destinations in the global South and (b) the role of the informal economy in shaping the context of reception for migrants in new gateway cities. Through surveys of Zimbabwean day labourers in Tshwane (formerly Pretoria), we document the poverty and the food and housing insecurity these migrants and their dependents endure resulting from underemployment in the informal economy. The analysis presented here suggests that although it has received little attention from migration scholars, the informal economy can play a significant role in shaping the context of reception for immigrants in the new gateway cities of the global South. In many destination countries, the informal economy absorbs large numbers of migrants, making it an important, if flawed, source of employment, earnings, and remittances. With increasing levels of migration to major cities, the informal economy has become a key arena of migrant incorporation, with far‐reaching implications for lives and livelihoods.